calculati (1-radical3)la2 +(1+radical3)la2-(1-radical3)(1+radical3)
Răspunsuri la întrebare
Răspuns de
2
(1-rad 3)^2=1-2*rad 3+3
(1+rad 3)^2=1+2 *rad 3+3
din suma lor rezulta=8
(1-rad 3)(1+rad 3)=1-3=-2
8-(-2)=10
(1+rad 3)^2=1+2 *rad 3+3
din suma lor rezulta=8
(1-rad 3)(1+rad 3)=1-3=-2
8-(-2)=10
Răspuns de
4
(1-√3)²+(1+√3)²-(1-√3)(1+√3)=
1-2√3+3+1+2√3+3-(1-3)=
8+2=10
1-2√3+3+1+2√3+3-(1-3)=
8+2=10
Alte întrebări interesante
Istorie,
8 ani în urmă
Fizică,
8 ani în urmă
Fizică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă